Cellular senescence marker p16INK4a and NFKB1 gene polymorphisms in lower gastro-intestinal acute graft versus host disease - Kuba, Adam; Raida, Ludek; Brychtova, Svetlana; Flodr, Patrik; Mrazek, Frantisek; Kriegova, Eva; Faber, Edgar; Papajik, Tomas (Transplant immunology, 2023)
BACKGROUND: Lower gastrointestinal (GI) graft versus host disease (GVHD) represents a severe complication in allogeneic hematopoietic stem cell transplant (HSCT) recipients with high rates of transplant-related mortality. Deregulated innate immunity reactions are the features of its pathogenesis. Cellular senescence has been considered a program of the innate immunity. We focused on lower GI GVHD from the perspective of cellular senescence. OBJECTIVE: We analyzed the impact of p16INK4a expression, a hallmark of cellular senescence, in intestinal biopsies of patients with lower GI GVHD symptoms and NFKB1 gene polymorphisms (rs3774937 C/T and rs3774959 A/G) on HSCT outcome. STUDY DESIGN: Fifty-two single-center patients who presented with symptoms of lower GI GVHD were analyzed in a retrospective manner. Two SNPs located in the NFKB1 gene regions (rs3774937 C/T and rs3774959 A/G) were genotyped from the peripheral blood samples collected before the start of the conditioning. All patients underwent proctosigmoidoscopy with biopsy of the mucosa. The expression of p16INK4a was analyzed in normal intestinal crypts and stroma. RESULTS: Fifty-two patients (50% male) received HSCT for hematological diseases (acute leukemias in 67%) and developed lower GI symptoms. Patients with p16INK4a expression in the intestinal stroma were in lower risk of developing histological grade 3-4 aGVHD (RR 0.18 [95% CI 0.05-0.65]; p = 0.009). The multivariate linear regression confirmed the independent effect of p16INK4a expression on time of the lower GI aGVHD symptoms onset (Coef. 38.9 [95% CI 12.7-65.1]; p = 0.005). The NFKB1 rs3774937 CC and TT/TC genotype were present in 40 and 80% of patients with p16INK4a expression, respectively (p = 0.04). The rs3774959 AA and GG/AG genotype were present among 43 and 82% of patients with p16INK4a expression, respectively (p = 0.02). Expression of p16INK4a was associated with no clinical variable but NFKB1 genotype. CONCLUSIONS: Our results address possible new mechanisms that may lead to better understanding of HSCT-related immune complications. Cellular senescence may bring novel approaches in GVHD diagnostics and therapy.
Keywords: gastrointestinální nemoci; retrospektivní studie; Retrospective Studies; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; lidé; NF-kappa B - podjednotka p50; NF-kappa B p50 Subunit; jednonukleotidový polymorfismus; Female; Cellular Senescence; Polymorphism, Single Nucleotide; Male; Graft vs Host Disease; ženské pohlaví; Humans; Cyclin-Dependent Kinase Inhibitor p16; mužské pohlaví; inhibitor p16 cyklin-dependentní kinasy; stárnutí buněk; nemoc štěpu proti hostiteli; Gastrointestinal Diseases